#TITLE_ALTERNATIVE# - IRWANSYAH, FAJAR
In information age, modern educational system ideally visualizes education in a way that gives learning opportunities at its highest possible options. It includes technological uses, information technology in particular. There are many ways to integrate subject into a comprehensive learning experience for children. One of them is the use of computer based learning system or e-learning. Computer based learning system or e-learning is a promising educational tool in improving subject proficiency, but designing an ideal computer based learning system is not an easy task. And the result has not been satisfactory, especially e-learning that is designed for children, because of their special characteristic, attracting their attention is a must. Children are easily distracted and not focus on certain subject, on the other hand playing and playing game can keep children for hours and let them undisturbed. Game approach in e-learning seems more promising for today's digital generation, because of its capabilities to enhance learning motivation with fun in the process. There are experts who believe that learning will be more effective if conducted in an enjoyable condition which initiates enthusiasm. It is more promising because basically children are game players. Also game has many benefits which can not be found in conventional teaching, especially the competency in creating a supportive learning environment, and at the same time improving cognitive skills specifically the role playing game genre. There are many studies that conclude a plus point of role playing game genre in creating a positive learning environment. There are many aspects in developing game that need attention and there is still a limited amount of research about game based learning model development, especially learning model with role playing game approach. This research will try to create a learning model prototype with role playing game approach by combining learning materials and fun in game. The main purpose of this research is to develop learning model with role playing game approach, furthermore it is expected to increase children's motivation in learning, math in particular, and improving math proficiency. This learning model is developed by adding in materials and curriculum into the game, and learning goals are deliberately hidden by game achievement goals. Nevertheless goal and achievement of the game are capable in facilitating curriculum needs (first grade elementary school curriculum), however this model prototype does not facilitate the entire needs of the curriculum Methods used in developing this learning model prototype with role playing game approach, can be described as followed: 1. Problem identification stage; deciding focus of problem on research that will be conducted. 2. Data collecting stage; exploring, data collecting and literature that support the research. 3. Analyzing stage; analyzing the development aspects of learning model which is mapped in framework form as groundwork of the next stage. 4. Designing stage; creating learning model concept that will be developed and making technical design of the development in form of software prototype and model screen design that will be made. 5. Implementing and testing stage; learning model prototype development stage with role playing game approach and testing a developed model. The developed learning model is an adventure in a fantasy world combating enemies for a rescue mission. In this adventure, the main character is helped by player to strike his enemies, by solving mathematical problems in form of adding and subtracting visualization. In general this learning model prototype is divided into two parts, the first part is battle visualization part and the second is mathematical problems visualization to accumulate striking points which used each time player has his/her turn to strike enemies. The result of testing that is done to this learning model prototype with role playing game that has been developed, shows that the built prototype is well functioned.